Disruption of T-even Bacteriophages by Dimethyl Sulfoxide - Cummings, Donald J. (1968)
Dimethyl sulfoxide (DMSO) disrupted T-even bacteriophages as well as λ bacteriophage. The component substructures of T2L, T4B01, or T6, in particular heads, were readily isolated after treatment with 67% DMSO (v/v). In contrast, concentrations of DMSO above 50% not only separated heads from tails of bacteriophage λ but led to degradation of the λ heads. Examination of the isolated free heads of T-even bacteriophage indicated that a distinct neck substructure was attached to one apex of the head. On some free tails a similar neck substructure was also found at the proximal end of the sheath. The dimensions of this neck substructure were found to be about 130 by 180 A; by virtue of its size and morphological attachment to the free heads, it was concluded that this was a distinct substructure and not an extension of the tail tube.